PERLINDUNGAN ANAK DALAM PERSPEKTIF HUKUM ISLAM DAN HAM - Siswadi, Imran (Al-Mawarid Jurnal Hukum Islam, 2010)
In Islamic Law and the Act of the Republic of Indonesia Number 23 of 2002, on protection of children. Such protection is the protection from acts of violence against children in the household. Because it is a violation of the rights of children, since it is incompatible with human values and religious teachings. In Islamic law and this law a childs rights are actually protected from the womb to age 18 years or until marriage. But from these two sources of law provides for tolerance "violence" as long as it does not affect on the physical and mental development as a means of education to the children, but still not violate the rights of a child. Both the Islamic Law and the Act No. 23 of 2002 regulates the protection of children in the womb until age 18. Keywords: hukum Islam, perlindungan anak, undang-undang, dan HAM